Legal harmonization, institutional quality, and countries' external positions: A sectoral analysis - Franziska Bremus; Tatsiana Kliatskova (Journal of International Money and Finance, 2020)
Motivated by the action plan for a European capital markets union (CMU), this paper analyzes the potential for legal harmonization and convergence in institutional quality to affect capital market integration. Based on hand-collected data on the implementation of EU-directives, our analysis yields three key insights. First, legal harmonization promotes portfolio equity holdings. Second, discrepancies in institutional quality matter primarily for cross-border debt positions. Third, the relationship between external investments and harmonization varies significantly across sectors: the non-bank financial corporations, which account for a large share of portfolio positions, react more to institutional harmonization than do banks and the non-financial private sector.
Keywords: E02; F21; G15; 330; Capital market integration; Legal harmonization; Sectoral effects